Kick-starting the Kisan Urja Suraksha evam Utthaan Mahabhiyan - Shah, Tushaar (2018)
The Union Budget 2018 announced the Kisan Urja Suraksha evam Utthaan Mahabhiyan, a scheme to replace diesel pumps and grid-connected electric tube wells for irrigation with solar irrigation pumps, including a buy-back arrangement for farmers’ surplus solar energy at a remunerative price. KUSUM can be a game changer as it can check groundwater over-exploitation, offer farmers uninterrupted daytime power supply, reduce the carbon footprint of agriculture, curtail the farm power subsidy burden, and provide a new source of risk-free income for farmers.